Multi-modal piezoelectric energy harvester - Wang, Nan (2017)
Wireless Sensor Nodes (WSNs) are widely used in Structure Health Monitoring (SHM) with the advantage of wireless communication. However, the limitation of service life from replacement/ recharge battery and high manual replacement frequency narrow the application of WSN in SHM. Piezoelectric energy harvesting system has been introduced and studied as alternate power source of the continuous self-power wireless sensing. Recent researches of energy harvester are designed as a cantilever beam with piezoelectric material. It was proven that resonant peaks can be achieved with array of harvester beams in wider bandwidth. The objective of this study is widening the operational bandwidth with the ultimate design of piezoelectric energy harvester. There are two prototypes of piezoelectric energy harvester. One of the prototypes is linear piezoelectric energy harvester and the other is multi-modal piezoelectric energy harvester comprised of a main aluminum cantilever beam bonded with MFC and three small branch beams attached parallel. FEM simulation with ANSYS is conducted first, which involves in comparisons the size of branch beam and weight of tip mass to determine ultimate design. The experiment results of harvester show that 3 peak power output will be obtained within 20Hz to 40Hz, and the bandwidth is widened as compared to linear harvester.